Financial Contagion from the Subprime Crisis: A Copula Approach - Mendes, Rita I.L. (2022)
The magnitude of the subprime crisis effects caused recessions in several economies, giving rise to the global financial crisis. The scale of this major shock and the different recovery profiles of European economies motivated this paper. The main objective is to look for evidence of contagion between the North American financial market (S&P500) and the financial markets of Portugal (PSI20), Spain (IBEX35), Greece (ATHEX) and Italy (FTSEMIB), in the South of Europe, and the financial markets of Sweden (OMXS30), Denmark (OMX2C0), Finland (OMXH25) and Norway (OsloOBX), in the North of Europe. Considering the period from January 1, 2003 to December 31, 2013, the ARMAGARCH models were estimated to remove the autoregressive and conditional heteroscedastic effects from the time series of the daily returns. Then, the copula models were used to estimate the dependence relationships between the European stock indexes and the North American stock index, from the precrisis subperiod to the crisis subperiod. The results indicate financial contagion of the subprime crisis for all analyzed European countries. The North European markets intensified the relations of financial integration (both in negative and positive shocks) with the North American market, apart from the Danish against the Portuguese. In addition to the contribution made by the joint application of the ARMA-GARCH models, the findings are useful to identify channels of financial contagion between markets and to warn about the effects of possible new crisis, which will require different levels of adaptation by the companies’ financial managers and intervention by the authorities.